BEHAVIORAL PRICE ON REVISIT INTENTION THROUGH MONETARY PRICE IN TYPE B PRIVATE HOSPITAL - Nico Harly Chandra (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The aim of this research is to determine the effects of service quality on monetary price, perceived waiting times on monetary price, behavioral price on monetary price, service quality on revisit intention, behavioral price on revisit intention and monetary price on revisit intention. This research was conducted using a quantitative research paradigm with a descriptive approach and hypothesis testing. The sampling method used a purposive non-probability sampling method with a total of 130 patients as respondents. Respondents who were included in the inclusion criteria in this study were patients who had received treatment at a type B private hospital in the North Jakarta area in the last 6 months and were over 19 years old. The results obtained were analyzed using PLS-SEM software. The results of data analysis show that service quality has a positive effect on monetary price, perceived waiting times has a positive effect on monetary price, behavioral price has a positive effect on monetary price, service quality has a positive effect on revisit intention to go to the hospital, behavioral price has a negative effect on revisit intention to go home illness and monetary price have a positive effect on revisit intention to go to the hospital. Through this research, hopefully can increase management in the hospital also can be used as theoretical reference for further research.